Urinary Incontinence in Men with Stroke: A Cross-Sectional Study - İsmail Uysal; Özgür Nadiye Doğrukök; Yalcin Golcuk; Fatih Özden; Mehmet Özkeskin; Miray Başer; Bircan Yücekaya; Zeynep Nisa Karakoyun (Medicina)
Background and Objectives: To evaluate urinary incontinence (UI) and its effect on quality of life (QoL) in male stroke patients. Materials and Methods: A quantitative cross-sectional study was conducted with 103 adult male stroke survivors. The individuals’ degree of disability was evaluated using the Modified Rankin Scale (MRS) and Barthel Index (BI). The UI assessment was performed with the Urogenital Distress Inventory (UDI-6) and the Incontinence Impact Questionnaire-7 (IIQ-7). In addition, the QoL was questioned with EuroQoL 5-Dimension 3-Level (EQ-5D-3L)”. Results: The mean age of the participants was 68.4 ± 9.9 years. The average scores of the IIQ-7 and UDI-6 were 9.7 ± 7.2 and 36.6 ± 26.3, respectively. According to these scores, both UI questionnaire results were slightly above the reference cut-off value. According to the UDI-6 scores, 52.4% of the participants exhibited symptoms, while 55.3% demonstrated symptoms according to the IIQ-7 scores. The IIQ-7 was strongly correlated with the MRS (p < 0.001, r = 0.740), BI (p < 0.001, r = −0.770), EQ-5D-3L Index (p < 0.001, r = −0.804), and EQ-5D-3L VAS (p < 0.001, r = −0.679) scores. In addition, the UDI-6 was strongly correlated with the MRS (p < 0.001, r = 0.697), BI (p < 0.001, r = −0.730), EQ-5D-3L Index (p < 0.001, r = −0.726), and EQ-5D-3L VAS (p < 0.001, r = −0.623) scores. Furthermore, the IIQ-7 and UDI-6 scores were statistically higher in patients with cortical-level involvement (p < 0.05). Regression results showed that the IIQ-7 was associated with the MRS, BI, EQ-5D-3L Index, and EQ-5D-3L VAS scores (R2 = 0.627, p < 0.001). Similarly, the UDI-6 was significantly associated with the MRS, BI, EQ-5D-3L Index, and EQ-5D-3L VAS scores in a multiple hierarchical regression model (R2 = 0.423, p < 0.001). Conclusions: The severity of UI was classified as high. As expected, UI was higher in individuals with increased disability. The QoL of individuals with UI is more negatively affected. Finally, the severity of UI was higher in individuals with cortical stroke.